Relation of interleukin-1β gene to treatment response in chronic patients infected with HCV genotype 4 - Moataza Hassan Omran; Noha E. Ibrahim; Samar S. Youssef; Basma E Fatouh; Wael Nabil; Magdy M El-Shami; Mostafa K El-Awady (Journal of Infection in Developing Countries)
Introduction: Hepatitis C virus (HCV) infection results in chronic hepatitis in more than 70% of infected patients, while 20-30% of patients recover spontaneously. This strengthens the role of the host genetic factors in either spontaneous or drug-induced viral clearance. The aim of this study was to investigate the relationship between interleukin-1β +3953 gene polymorphism and the response to interferon therapy in chronic HCV patients infected with genotype 4. Methodology: The interleukin-1β (+3953 C/T) (rs1143634) gene was amplified in 115 chronic HCV patients. Interleukin-1β single nucleotide polymorphism (SNP) plus several clinical and pathological factors were statistically analyzed in correlation with response to therapy. Results: Genotypes C/T and T/T had a significant association with non-response to treatment compared to genotype C/C, which had a strong association with response to treatment (95% confidence; 6.4884-48.5818, p = 0.0001). Furthermore, analysis of allele frequency in this cohort revealed that the T allele is associated with non-response, higher fibrosis, and higher hepatic activity, while the C allele had a significant association with sustained virologic response lower fibrosis, and lower hepatic activity (p value = 0.0001). Conclusion: This is the first study to examine the correlation between interleukin-1β (+3953 C/T) (rs1143634) gene polymorphism and the response of interferon therapy in genotype 4 HCV-infected patients. The results encourage further assessment of this SNP as a marker  to predict response to therapy and disease progression, which can have major implications in saving money, time, and in avoiding unnecessary adverse effects.